(untitled) (Bangladesh Journal of Plant Taxonomy, 2016)
A multivariate statistical analysis was carried out to evaluate the morphological variation between Nymphaea pubescens Willd., and a deep purplish red flowered Nymphaea that occur in Sri Lanka. The plant resembles N. rubra Roxb. ex Andrews, a species that had been sometimes circumscribed as a variety under N. pubescens Willd. DNA sequences data of matK and psbA-trnH regions were used to obtain further support. Morphological data were scored from collected samples and analyzed using PAST software. Extracted DNA were amplified for matK and psbA-trnH gene regions. Obtained sequences were matched with the related accessions deposited in the GenBank. Multivariate analysis supported the recognition of deep purplish red flowered Nymphaea as a different species from N. pubescens, and was identified as N. rubra based on literature. GenBank accessions for the matK region of N. rubra showed 99% similarity while it gave only a 96% similarity for N. pubescens with query coverage of 97% and 96% respectively, corroborating with the morphological analysis. Comparison of the sequence divergence between N. pubescens and N. rubra sequences indicated a 95% similarity for matK gene region while 92% similarity for psbA-trnH gene region. The sequences generated during the present study would provide additional reference sequences for the two taxa. Bangladesh J. Plant Taxon. 23(2): 107-117, 2016 (December)